Griffith–Kelly–Sherman correlation inequalities for generalized Potts model - Ganikhodjaev, Nasir; Abdul Razak, Fatimah (2010)

(untitled)
Inspired by the work of D.G.Kelly and S.Sherman on general Griffiths inequalities on correlations in Ising ferromagnets, we formulate and prove Griffith–Kelly–Sherman-type inequalities for the ferromagnetic Potts model with a general number q of local states. We take as local state space for the q-state Potts model the set Fc ={-l, -l+1, · · · ,l -1,l},where l= (q-1)/2. The important properties of Fc for what follows are that |Fc | = q and Fc = -Fc